TRENDS OF AUTOPSY CASES DURING COVID-19 PANDEMIC RESTRICTIONS (Journal of Forensic Medicine & Toxicology, 2022)
COVID-19 leads to a serious impact on health of people worldwide which not only as a direct consequence of the infection but also due to the measures taken to reduce its transmission. The present study was conducted at Government Medical College Patiala .The aim of our study was to identify and compare the characteristics of cases Organization (WHO)has declared a global health emergency due to this.1 COVID-19 leads to a serious impact on health of people worldwide which not only as a direct consequence of the infection but also due to the measures taken to reduce its transmission. These unparalleled changes in the lifestyles has impacted mental health and society in many ways.2 On the evening of 24 March 2020, the Government of India under Prime Minister ordered a nationwide lockdown which extended up to 31 may 2020 in 4 phases after that partial unlocking was started. A second wave beginning in March 2021 was much larger than the first and lockdown was imposed by different sates depending upon the case load.3
Keywords: estimates; approximately; global